Glycyrrhetinic acid-modified chitosan nanoparticles enhanced the effect of 5-fluorouracil in murine liver cancer model via regulatory T-cells [Retraction] - Cheng M; Xu H; Wang Y; Chen H; He B; Gao X; Li Y; Han J; Zhang Z (Dove Medical Press, 2014)
Cheng M, Xu H, Wang Y, et al. Drug Des Devel Ther. 2013;7:1287–1299. It has come to the notice of this journal that the published paper:Cheng M, Xu H, Wang Y, et al. Glycyrrhetinic acid-modified chitosan nanoparticles enhanced the effect of 5-fluorouracil in murine liver cancer model via regulatory T-cells. Drug Des Devel Ther. 2013;7:1287–1299. Plagiarised the work of:Cheng M, Gao X, Wang Y, et al. Synthesis of Glycyrrhetinic Acid-Modified Chitosan 5-Fluorouracil Nanoparticles and Its Inhibition of Liver Cancer Characteristics in Vitro and in Vivo. Marine Drugs. 2013;11(9):3517–3536.The first author, Mingrong Cheng, brought this to our attention, has admitted the fault was his own, due to lack of experience and understanding, and apologized.                    Accordingly Dove Medical Press issue the retraction for Cheng M, Xu H, Wang Y, et al. Glycyrrhetinic acid-modified chitosan nanoparticles enhanced the effect of 5-fluorouracil in murine liver cancer model via regulatory T-cells. Drug Des Devel Ther. 2013;7:1287–1299.